PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF PADA MATERI REAKSI REDOKS UNTUK MENINGKATKAN PEMAHAMAN KONSEP PESERTA DIDIK - Sherly Ernita; Rina Elvia; Hermansyah Amir (ALOTROP, 2023)
This study aims to improve students' understanding of the concept of redox reactions using interactive learning media. The results of the development are measured in terms of the level of validity, learning outcomes as seen from the N-gain score, as well as the responses of students and educators. The development model used is the ADDIE model. The subjects for the product trial were 12 students in class XI MIPA 6 and the subjects for product application were class XI MIPA 7 with 36 students. The research instruments were interview sheets, product validation questionnaires, questions, student and educator response questionnaires, pre-test, post-test. The results of media and material validation were 95%, 91.42%, respectively, the two validity percentages were rated as very valid. The results of the validation of questions > 2.34 were considered feasible, the student response of 86.66% was in the very good category. The N-Gain obtained was 0.657 which was categorized as a moderate increase. The results of the educator's response to the product that has been developed is 94.33% which is in the very interesting category. Based on the results of the research concluded, interactive learning media can improve students' understanding of concepts. Keywords: Research and Development; Interactive Learning Media; Understanding Concept; Redox Reaction; Ispring Suite 11